Larvicidal Activity of Brusatol Isolated from Brucea javanica (L) Merr on Culex quinquefasciatus - Dwi SUTININGSIH; Nurjazuli NURJAZULI; Djoko NUGROHO; Tri Baskoro Tunggul SATOTO (Tehran University of Medical Sciences, 2019)
Background: Vector control is still emphasized on the using of chemical insecticide which can cause death of non-target organisms, pollution and vector resistance. Therefore, natural insecticides/larvicides are an alternative to using chemical insecticides to control the mosquito vector. Methods: Brusatol was isolated from the seeds of Makassar Fruit (Brucea javanica L. Merr). Culex quinquefasciatus larvae were divided into 3 groups, i.e. 6 testing groups and one negative and positive control group. In the negative control group, the larvae were treated with 100 ml aquadest and positive control was treated with temephos 1 ppm. After 24 hours, dead larvae were calculated and the percentage of death was determined. The dead larvae were then examined for morphological changes using a light microscope. Results: The higher of the concentration level of brusatol, the higher number of the death of Cx. quinquefasciatus larvae (P<0.05). The value of brusatol Lethal Concentration 50 to larvae Cx. quinquefasciatus was 0.010 ± 0.122 and value of brusatol Lethal Concentration 90 to larvae Cx. quinquefasciatus was 0.654 ± 0.081 ppm. The higher the concentration of brusatol, the morphological damage of Cx. quinquefasciatus larvae was getting worse and widespread to cause damage to the digestive tract and cuticle. Conclusion: Brusatol isolated from the seed of B. javanica (L) Merr have larvicidal activity to the Cx. quinquefasciatus which is potential to be natural larvicide.